Glymphatic dysfunction assessed by DTI-ALPS index predicts early cognitive impairment in acute subcortical infarcts: a prospective clinical cohort study - Yirong Wang; Mei Yang; Xingmao Zeng; Shuai Wang; Wenmin Zhang; Weidong Wang; Yang Du; Jurong Ding; Xin Ding (Frontiers in Neurology)
BackgroundThe glymphatic system (GS), responsible for clearing neurotoxic proteins (such as β-amyloid and tau protein), is critical in stroke pathophysiology. However, its role in acute post-stroke cognitive impairment (PSCI) remains unclear. We investigated GS dysfunction via the DTI-ALPS index in acute subcortical infarct patients and its association with early cognitive decline.MethodsThis prospective cohort included 29 subcortical infarct patients and 25 healthy controls (HC). Participants underwent 3.0 T MRI (DTI/structural sequences) and Montreal Cognitive Assessment (MoCA) at 7 and 90 days post-stroke. Bilateral DTI-ALPS indices were calculated. Group comparisons and Spearman correlations were analyzed.ResultsThe DTI-ALPS index of the lesion (1.371 ± 0.170) and non-lesion side (1.310 ± 0.198) in the SI group were significantly lower than that in HC group (1.568 ± 0.115) (both of p < 0.001, respectively). While, the DTI-ALPS index of the lesion side was no significant difference than that of the non-lesion side in subcortical infarct group (p = 0.214). The scores of MoCA in 7 days and 90 days after stroke were significantly lower than those in HC group (p < 0.001). In patients with subcortical infarct, MoCA scores at 7 days showed significant correlation with lesion-side DTI-ALPS index (r = 0.510, p = 0.005) but not with non-lesion DTI-ALPS values (r = 0.174, p = 0.259). Notably, we observed significant correlations between MoCA scores at 90 days post-stroke and DTI-ALPS index, which were consistently demonstrated in the lesion, non-lesion, and mean bilateral measurements. The ROC analysis demonstrated that the DTI-ALPS index showed moderate discriminative ability (AUC = 0.868) in differentiating patients with cognitive impairment from those with normal cognition following subcortical infarction, exhibiting excellent sensitivity (96.0%) but suboptimal specificity (65.5%).ConclusionIschemic stroke leads to glymphatic dysfunction, which is associated with early post-stroke cognitive impairment.